Should English for Teaching Mathematics and Science (ETeMS) in Malaysia be abolished? - Mohamad Nor, Faizah; A. Aziz, Marzilah; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
ETeMS (or English for Teaching Mathematics and Science) was introduced in Malaysia in 2002 to enhance the English language skills of Malaysian learners. The move has however mooted much debate as non-proficient learners were said to have been affected by this regulation as they are said to have fared badly in Mathematics and Science, since the two subjects were taught in English. Following the controversy over ETeMS, in 2010, the Malaysian government decided to revert to teaching Mathematics and Science in the national language, beginning 2012. This research was thus undertaken to gauge the views of learners on learning these subjects in English. The main objectives of the research are to find out if the learners had improved in English, as a result of this move and whether their performance in Mathematics and Science had improved or deteriorated as a consequence of having to learn the subjects in English. The main research instrument used was questionnaires which were distributed to students of a reputable boarding school in Malaysia. It is hoped that the findings of this study would help justify the decision the policy makers have with regard to ETeMS.